Children of the dragon : Selected tales from Vietnam - Garland, Sherry (Harcourt, Inc., 2001)
The book recounts three Vietnamese folk tales. These colorful tales depict heroes, ancient kings, famous battles, and tribal customs, and are all vividly rewritten in stunning full-color images brilliant colors.